Impacto da saúde bucal na qualidade de vida de adolescentes grávidas - Lima, Daniela Pereira [UNESP] (2014)
In Brazil the number of teenage pregnancies has increased significantly and is considered a public health problem. Pregnancy in adolescence is a time of risk for oral health due to the potential increase in the consumption of sugary foods and behavioral changes, and there may be negligence in oral hygiene. The objective of this study was to evaluate the impact of oral health on the quality of life of pregnant adolescents, assess the health indicators by determining the experience of dental caries and periodontal examination and self-perceived oral health status and to evaluate the association between the studied variables. A transversal study, survey type and survey of the oral health status of 127 adolescents 10-19 years of age, pregnant women, accompanied by the Unified Health System Araçatuba-SP were performed. Questionnaires were administered and oral examinations were conducted. To measure the impact of oral health on the quality of life, the Oral Health Impact Profile (OHIP-14) was used, and the self-perceived oral health and socio-demographic data were recorded using an adapted questionnaire. The DMFT, SiC-Index and CPI indices were used according to the criteria established by the WHO. Descriptive statistical analyses and the Fisher's exact test with a significance level of 5% were conducted, as well as the logistic regression analysis to verify the association between variables. The vast majority, 79.5% reported impacts of oral health conditions in their quality of life. The items that demonstrated the greatest impact were: pain (23.6%) and discomfort with feeding (18.9%) felt due to oral problems. The items of the domains: social disability (88.9%) and social disadvantage (89.7%) were those that detected less impact on the lives of young people. Of the total, 41.0% reported having a satisfactory oral health, while 63.0% believed...